Molecular and Histological Study of the Effect of Trade Pesticide Chlorpyrifos on Mature Male Rats . - A.M., Mohammed; Th.M., Wijdan (Al-Qadisiyah Journal of Pure Science, 2018)
study the concentration and parameters of sperm and also the area was femurs eradicated and the greatness of the tibia of the leg to the test animals for the purpose of the study of cell division coefficient and chromosomal aberrations of the nuclei of the bone marrow cells were sacrificed on the stages of technology topics studied parts .pent results occurrence of a significant decrease in body weight of animals treated with pesticide the doses 1/0, / 20 mg / kg of body weight and for a period of 14 days from the pesticide Chlorpyrifos while there was a decrease in the gain weighted for the group treated at a dose of 30.1 mg / kg of body weight rate for the same period at a level of probability (P <0.05) . for the weight of the brain first and second groups for a period of 14 days, it was noted the existence of a significant increase between the second and third groups for a period of 14 days and a significant level of P <0.05. The study showed a clear appearance of a decrease significantly in the division coefficient totals injections all rates for 14 days and observed no significant difference level of significance P <0.05 between the totals for the first study and the second with a control group for a period of 7 days,. were examined studied segments of the bone marrow and the results showed deformities chromosomal, few chromosomal number, the decay of chromosomal, cases of adhesion, chromosome annular chromosomal . results doubled to prepare sperm rates of less significance to the totals for the injection of all for a period of 7 days was observed significant decrease significantly the level of P <0.05 in sperm rates and totals for the injection of all for the period 14 days.